ANALISIS PENGARUH BAHASA GAUL DI KALANGAN SISWA SD KELAS RENDAH TERHADAP PENGGUNAAN BAHASA INDONESIA - Nur Wahyuni (Jurnal Sentra Pendidikan Anak Usia Dini, 2022)
The rapid development of the flow of technology and media has had an impact on various sectors in society, one of which is the use of good and correct language. Nowadays, especially among elementary school students, a new trend is emerging, namely slang. Slang is a language that students usually use by using cool terms in everyday speaking. Some examples of slang vocabulary are "mantul", "santuy", and so on. The use of language causes polemics in society towards the development of Indonesian language among lower grade elementary school students. The purpose of this study was to determine the effect of slang on Indonesian, to determine slang vocabulary, the development of slang among lower grade elementary school students, as well as the positive and negative impacts of slang. The method used in data collection uses a survey method given to several respondents and also a literature study method obtained from books, magazines, and the internet related to the problems being studied. The novelty in this study is the use of slang on the development of Indonesian among lower grade elementary school students.